Entre o mar e o continente - Silva Júnior, Moisés Rodrigues da (Percurso, 2017)
Realização: Ana Claudia Patitucci, Bela M. Sister, Cristina Parada Franch, Danielle Melanie Breyton, Deborah Joan de Cardoso e Silvio Hotimsky.